Siaga Village which is able to Provide Baby SPA Services as an Effort to Overcome Toddler Health Problems Without Medication in Order to Increase Health Independence in Karangwedoro Village, Turi District, Lamongan Regency - Kustini; Ida Susila; Eka Sarofah Ningsih (Universitas STRADA Indonesia, 2025)
Self-medication is an effort made by the community to treat symptoms of illness or disease using medication without a doctor's prescription. Nowadays, people more often practice self-medication by buying chemical medicines at pharmacies for health problems experienced by their toddlers without knowing the side effects that can be caused. In society, so far, baby spas have only focused on children's growth and development to fulfill the rights of children with special needs and monitor children's development according to age. In the midst of the many people who want services to overcome the health problems of toddlers (sick toddlers), we hope to be able to develop services to meet these needs by adhering to the principle of complementary services with the existence of Baby Spa training which is one of the efforts to handle toddler health problems comprehensively. Complement before using chemical drugs, the samples used were 40, with a total sampling technique. From the results of this training and counseling, it is hoped that it can increase the knowledge of mothers of toddlers regarding baby spas as an effort to handle toddler health problems before seeking treatment at a health facility, research analysis using qualitative analysis techniques.